2021
DOI: 10.1002/joc.7378
|View full text |Cite
|
Sign up to set email alerts
|

Observed and projected trends in climate extremes in a tropical highland region: An agroecosystem perspective

Abstract: Tropical highland environments present substantial challenges for climate projections due to sparse observations, significant local heterogeneity and inconsistent performance of global climate models (GCMs). Moreover, these areas are often densely populated, with agriculture‐based livelihoods sensitive to transient climate extremes not always included in available climate projections. In this context, we present an analysis of observed and projected trends in temperature and precipitation extremes across agroe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 69 publications
(84 reference statements)
0
3
0
Order By: Relevance
“…Under the influence of unstable factors such as frequent global extreme weather events and complex changes in the supply chain of agricultural products, how to increase food yield and improve agricultural production efficiency is an important global issue to ensure regional food security and social stability [ 1 , 2 , 3 ]. As a basic industry, agriculture has assumed an important role in maintaining social harmony and healthy development of the people under the pressure of China’s large base population.…”
Section: Introductionmentioning
confidence: 99%
“…Under the influence of unstable factors such as frequent global extreme weather events and complex changes in the supply chain of agricultural products, how to increase food yield and improve agricultural production efficiency is an important global issue to ensure regional food security and social stability [ 1 , 2 , 3 ]. As a basic industry, agriculture has assumed an important role in maintaining social harmony and healthy development of the people under the pressure of China’s large base population.…”
Section: Introductionmentioning
confidence: 99%
“…Overall, it appears that the timing of the shift in ENSO teleconnections between boreal summer and boreal fall is a difficult dynamic for models to capture in a consistent way. This has considerable implications for projections of future climate impacts in the uBN, where the end of the rainy season is critical for a number of agricultural activities (Zeleke et al ., 2017; Ademe et al ., 2021).…”
Section: Resultsmentioning
confidence: 99%
“…PRCPTOT showed a positive trend in all AEZs except for the hot arid AEZ, with the highest magnitude (15.25 mm/year) exhibited in the cool sub-humid AEZ. Nevertheless, a study conducted in tropical highlands at Choke Mountain reported a decreasing trend in PRCPTOT over warm semi-arid and cool sub-humid AEZs [56].…”
Section: Trends In Extreme Rainfall Indices Within Agro-ecological Zonesmentioning
confidence: 93%